Cuerpos digitales, cuerpos virtuales : investigaciones y creaciones que vinculan las artes escénicas y las nuevas tecnologías de la imagen - Ariza Gómez, Daniel (Colección Artes y humanidades., 2019)
"The present book shows the reader throughout different essays and interviews, the way a theorization has been generated around the scenic creations (which could be called contemporary scenic aesthetics) done between 2011 and 2016 at the University of Caldas (Manizales, Colombia) and the way in which the body has been put on stage through the use of different technological tools. That is why, the text becomes a space that reveals the way in which the research and creation processes were assumed, while at the time that each of the works are described in general." (HKB Translation) --Page 17